Jet and Tropopause Products for Analysis and Characterization (JETPAC) - Daffer, William H.; Manney, Gloria L. (2012)
This suite of IDL programs provides identification and comprehensive characterization of the dynamical features of the jet streams in the upper troposphere, the lower stratospheric polar night jet, and the tropopause. The output of this software not only provides comprehensive information on the jets and tropopause, but also gives this information in a form that facilitates studies of observations in relation to the jets and tropopauses.